El deseo como motor de acción en la obra Caza de conejos de Mario Levrero - Yaguana Jarro, Lady Elizabeth (2024)
The desire is one of the most frequent themes in literature because it is an integral part of the human condition. Therefore, the general objective of this research is to analyze the manifestations of this desire in the characters of the work "Caza de conejos" by the writer Mario Levrero. To achieve this, it identifies the desired objects and the ways in which desire is expressed in the characters of the narrative. Also, it characterizes the actions and relationships that the characters establish driven by desire. The methodological design of this work responds a qualitative approach, specifically, it is a literary analysis that adopts a post-structuralist perspective. Post-structuralism is a theoretical framework that considers the literary text as a source of multiple readings intersected by discourses available about reality. It also allows for the interpretation of the narration, especially the discourses and themes related to desire, in various ways and from other disciplines. In this case, the disciplines that inform the analysis are psychology and philosophy. Considering the specific objectives, the analytical categories include desired objects, manifestations of desire, actions, and relationships of the characters driven by desire. Furthermore, it is important to note that this analysis focuses on narrative elements such as characters and actions. The most relevant results indicate that desire in the novel "Caza de conejos" is presented as the main important key behind the characters' actions and behaviors, leading them towards desired objects such as the female body, the rabbit, and the phallus. However, this desire is never fully satisfied because the rabbit, which is the primary object of their desire, remains unachievable. and it is precisely this that leads to new actions constantly occurring such as devising and setting up traps of different types, erotic or violent actions, all of these are carried out in cooperative relationships or in competitive relationships between the characters. Similarly, this allows desire to manifest itself through erotic language, daydreaming, impulsiveness, and other forms. All of these actions and relationships exemplify what Deleuze and Guattari (1985) refer to as the rhizomatic and productive nature of desire.